Most Recent Trials and Advances in Hypertension - Elías Martínez Rey-Rañal; Alberto Cordero (European Cardiology Review)
Hypertension is one of the most prevalent cardiovascular risk factors and blood pressure control remains a clinical challenge, especially for patients with established cardiovascular disease. Late-breaking clinical trials and other evidence in hypertension have evolved to assess the most accurate ways to measure blood pressure, the use of combination therapies, considerations in special populations and evaluation of new techniques. Recent evidence supports the superiority of ambulatory or 24-hour blood pressure measurements, rather than office blood pressure measurements, for the assessment of cardiovascular risk. The use of fixed-dose combinations and polypills has been demonstrated to be valid and to provide clinical benefits beyond blood pressure control. There have also been advances in new approaches such as telemedicine, devices and the use of algorithms. Clinical trials have provided valuable data on blood pressure control in primary prevention, during pregnancy and in the elderly. The role of renal denervation remains unsolved but innovative techniques using ultrasound or alcohol injections are being explored. Current evidence and results of latest trials are summarised in this review.